Gratitude and life satisfaction in early adolescence: The mediating role of social support and emotional difficulties. (1st August 2018) - You, Sukkyung; Lee, June; Lee, Yunoug; Kim, Euikyung
Abstract: The current study examined the relationship between gratitude and life satisfaction among 877 Korean adolescents, and the mediating effects of social support and emotional difficulties in the relationship. The study's results revealed that those experiencing higher gratitude during early adolescents reported having more feelings of positive life satisfaction. Furthermore, social support and emotional difficulties were found to mediate the relationship between gratitude and life satisfaction. Findings suggested that grateful students perceived that more social support were available and experienced less emotional difficulties, in turn experiencing increased life satisfaction. Gender differences were not found in the relationship between gratitude and life satisfaction. Implications and future directions are also further discussed. Highlights: Grateful students perceived more social support were available. Grateful students perceived experienced less emotional difficulties. Social support mediates the relationship between gratitude and life satisfaction.